Improving DNA Vaccine Performance Through Vector Design - A. Williams, James (Current Gene Therapy, 2014)
DNA vaccines are a rapidly deployed next generation vaccination platform for treatment of human and animal disease. DNA delivery devices, such as electroporation and needle free jet injectors, are used to increase gene transfer. This results in higher antigen expression which correlates with improved humoral and cellular immunity in humans and animals. This review highlights recent vector and transgene design innovations that improve DNA vaccine performance. These new vectors improve antigen expression, increase plasmid manufacturing yield and quality in bioreactors, and eliminate antibiotic selection and other potential safety issues. A flowchart for designing synthetic antigen transgenes, combining antigen targeting, codon-optimization and bioinformatics, is presented. Application of improved vectors, of antibiotic free plasmid production, and cost effective manufacturing technologies will be critical to ensure safety, efficacy, and economically viable manufacturing of DNA vaccines currently under development for infectious disease, cancer, autoimmunity, immunotolerance and allergy indications.
Keywords: vector